Implementasi Fitrah Based Education dalam Pembelajaran Matematika Pada Materi Bangun Datar di Kelas V MIS Mutiara Aulia - Muthia Arini Hasibuan; Rora Rizky Andini; Nabila Azzahra (Constructivism: Journal of Research in Education, 2024)
This study aims to analyze the implementation of the Fitrah Based Education (FBE) method in mathematics learning for fifth-grade students at MIS Mutiara Aulia. The study employed a qualitative approach using descriptive research. The research subjects consisted of 30 fifth-grade students. Data were collected through observation, documentation, and literature study. The collected data were analyzed using descriptive qualitative analysis through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the Fitrah Based Education method in mathematics learning can create a more active, creative, and meaningful learning process. In the learning activity on plane geometry material, students were asked to draw various plane shapes and combine them into a ship model. This activity encouraged students to explore their creativity while understanding mathematical concepts more concretely. The findings also indicate that most students showed enthusiasm and active participation during the learning process. However, several challenges were identified, such as differences in students’ abilities and the lack of learning tools brought by some students. Overall, the application of the FBE approach can support the development of students’ creativity, learning motivation, and conceptual understanding in mathematics learning at the elementary school level